Docetaxel-Induced Stevens-Johnson Syndrome in a Patient with Metastatic Prostate Adenocarcinoma - Osama Diab; Dan Mcentire; Thamer Kassim; Ali Nayfeh; Abdel Rahman Dajani; Mitchell Kerfeld; Jonathon Campbell; Adbullah Alsuwaidan; Mahmoud Abu Hazeem; Maryam Gbadamosi-Akindele (Case Reports in Oncological Medicine)
Docetaxel is a commonly used chemotherapeutic agent in a variety of cancer treatment regimens. We present a case of apparent docetaxel-induced Stevens-Johnson syndrome (SJS) in a patient recently treated for metastatic prostate cancer. This medication is not classically associated with the development of SJS but in our case, along with a number of other case reports, and a single phase II clinical trial, an association was recognized. We encourage clinicians who employ the use of this medication to be aware of this relationship.